Occurrence and spatial distribution of 158 pharmaceuticals, drugs of abuse and related metabolites in offshore seawater - Alygizakis, Nikiforos A.; Gago-Ferrero, Pablo; Borova, Viola L.; Pavlidou, Alexandra; Hatzianestis, Ioannis; Thomaidis, Nikolaos S. (The Science of the total environment, 2016)
The occurrence and spatial distribution of 158 pharmaceuticals and drugs of abuse were studied in seawater of the Eastern Mediterranean Sea (Saronikos Gulf and Elefsis Bay in central Aegean Sea). This area is affected by various anthropogenic pressures as it receives the treated wastewater of the greatest Athens area and off-shore input fluxes. This study constitutes the largest one in terms of number of analytes in this environmental compartment. It provides the first evidence on the occurrence of several pharmaceuticals in marine environment including amoxicillin, lidocaine, citalopram or tramadol, among others. 22 samples were collected at three different depths in 9 sampling stations in order to assess the presence and the spatial distribution of the target compounds. A multi-residue method based on solid phase extraction and liquid chromatography coupled to tandem mass spectrometry was developed for the determination of the 158 target substances and validated for seawater sample analysis. 38 out of the 158 target compounds were detected, 15 of them with frequencies of detection equal to or higher than 50%. The highest detected values corresponded to amoxicillin, caffeine and salicylic acid, with concentrations in the range of <5.0–127.8ngL−1; 5.2–78.2ngL−1 and <0.4–53.3ngL−1, respectively. Inputs from the wastewater treatment plant (WWTP) of Athens revealed to be the main source of pollution in the Inner Saronikos Gulf, whereas, other anthropogenic pressures such as contamination from shipping activity, industrial effluents, dredging and/or inputs from land proved to be also relevant. Τhe concentrations of some compounds varied significantly with depth suggesting that currents play an important role in the dilution of the target compounds. [Display omitted] •This is the largest study of emerging contaminants (158) in seawater.•Thirty eight compounds have been detected.•Amoxicillin, salicylic acid and caffeine showed the highest concentration levels.•Wastewater release proved to be the major source of contamination.